RELASI DAN EKSISTENSI LAKI-LAKI DAN PEREMPUAN SEBAGAI GAMBAR RUPA ALLAH MENURUT KEJADIAN 1:26-28 - Grecetinovitria Merliana Butar-butar (Jurnal Teologi Cultivation, 2018)
Abstract The P Source tells us that God created man in His image and likeness (Gen 1: 26-27), which makes man different from other creations. In understanding the position of men and women, it is necessary to understand the great difference between the ideal picture (perspective) and the factual state. By that difference, this becomes the background of this research, the writer uses method Library Researc method and build a hypothesis "man and women as the Image of God is the ideal relationship embodied in its duties and responsibilities ". Keywords: Male, Female, Image of God.